(untitled) - Suzuki, Toshio (Tokyo, 2018)
Toshio Suzuki has devoted himself to Studio Ghibli for some thirty years, producing such world-renowned animated classics as Princess Mononoke and Spirited Away. Early in his career he met the two genius directors Hayao Miyazaki and Isao Takahata and gained their confidence. Working with these two inimitable directors, he experienced the joys and sorrows of filmmaking, and he continues today to guide the studio. Based on his innate inquisitive nature and the accumulated resources of thirty years, Suzuki has recounted in this book the story not only of Miyazaki and Takahata but also the other figures working at Studio Ghibli or in connection with it. It is a fascinating tale, told with penetrating insight and heartwarming humor.
Keywords: Phim ngắn,Short fiml